The role of liver microenvironment in hepatic metastasis. Issue 1 (1st July 2019) - Williamson, Tovah; Sultanpuram, Nikhila; Sendi, Hossein
Abstract: Metastasis is still poorly understood and thus further research must be conducted to provide insight into the driving factors. Novel research has revealed the significance of the microenvironment in the delegation of metastasis, expanding the field of cancer metastasis to cells and cell environments surrounding the migrated tumor cells. Research on hepatic metastasis is an ever‐growing domain of this field, as several primary tumors can metastasize to the liver. The two features within the liver that promote metastasis—cellular and acellular—are found in the current interpretation of liver microenvironment. Novel findings of both are included in this review. Different hypotheses detailing the methods by which metastasis can occur must be included to understand the significance of the microenvironment, as well as a brief overview of the methods that can be used during research. This review aims to highlight the importance of liver microenvironment on the development or potential regression of hepatic metastasis through discussing both acellular and cellular components of liver microenvironment and their interaction with metastasis.